Relationship between Gold Futures Open Interest and Gold Futures Returns - Vijayalakshmi, D.; Manasha, S. (Indian Journal of Research in Capital Markets, 2023)
Purpose : The present study analyzed the trend in open interest and the relationship between gold futures open interest and futures returns to examine the investors’ preference for gold commodity investment for asset allocation in their portfolio. Participants and investors in the commodity market strongly believe that open interest plays an essential role in determining the prices of commodity futures. To account for this, we studied the relationship between gold commodity futures open interest and gold futures returns. Methodology : Futures returns was a dependent variable, while open interest was an independent variable in the study. E-views software 10.0 version acquired daily data on open interest in gold commodities and futures daily prices from 2012 to 2020 from the multi-commodity exchange (MCX) website. Findings : We found no relationship between gold futures open interest and futures returns, and temporal trends like seasonal components did not impact open interest. Practical Implications : It was advised that investors and portfolio managers use the results of the current study to help them determine their asset allocation. Our study had significant limitations, but it also leaves room for future research into the function and effectiveness of e-gold investments. The study might include additional investment classes if given a compelling structure. Originality : In contrast to earlier studies on investment in gold commodities, the current study examined the relationship between open interest and futures prices and developed a model to comprehend investors’ rising desire for gold commodities.